The Role of Multidisciplinary Teams in Managing Severe Trauma in Emergency Settings: Optimizing Coordination and Care - Rather, Irfan Habib; Tarifi, Ayman Othman; Hafeez, Umair; Rather, Haseeb Javaid; Ain, Qurat ul; Rather, Sanaan Ajaz; Rather, Ajaz Ahmad (Journal of Fatima Jinnah Medical University, 2024)
Background: Trauma is a leading cause of morbidity and mortality, especially in resource-limited settings with limited infrastructure and personnel. Multidisciplinary trauma teams (MDTs) are crucial for effective management, yet their implementation in such environments faces challenges. This study evaluates the impact of MDTs on patient outcomes and identifies strategies to enhance trauma care in resource-constrained settings. Patients and Methods: This retrospective study included 90 adults with severe trauma admitted to the A&E. Patients were categorized based on the quality of multidisciplinary team care: MDT-Optimized (coordinated, timely interventions) and Non-Optimized (delayed or incomplete interventions). Data were collected on demographics, injury details, and outcomes from electronic medical records, focusing on in-hospital mortality, morbidity, hospital stay, and time to treatment. Results: Of the 90 patients studied, 74.4% had blunt trauma, primarily from road traffic accidents and falls. The mean Injury Severity Score (ISS) was 23.5. Sixty-four percent received MDT-Optimized Care, while 36% experienced delayed or incomplete care. The MDT-Optimized group had faster times to surgical intervention (2.4 vs. 4.1 hours) and initial stabilization (12.5 vs. 24.8 minutes). Mortality was lower in the MDT-Optimized group (5.2% vs. 28.1%) and morbidity was reduced (15.5% vs. 59.4%). Hospital stays were shorter (9.6 vs. 14.3 days), and recovery outcomes were better, with 82.8% of MDT-Optimized patients discharged with full recovery or mild disability compared to 50% in the Non-Optimized group. Multivariate analysis highlighted ISS >25, delayed surgery, and lack of MDT coordination as factors increasing mortality and morbidity. Conclusion: In conclusion, this study demonstrates that the involvement of multidisciplinary teams in managing severe trauma in emergency settings significantly improves patient outcomes, including reduced mortality, lower complication rates, shorter hospital stays, and better recovery. The findings are in line with previous studies and underscore the necessity of implementing well-coordinated, team-based approaches to trauma care, particularly in resource-limited environments.